PENINGKATAN MINAT DAN KETERAMPILAN MENULIS WANGSALAN DENGAN MODEL MAKE A MATCH DAN MACROMEDIA UNITY PADA SISWA KELAS XI IPA 3 SMA NEGERI 1 NGEMPLAK BOYOLALI - Prayogo, Hannif Purwo; Rahadini, Astiana Ajeng; Sumarwati, Sumarwati (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2017)
The objectives of this research are to increase the quality of learning process in writing wangsalan and students’ wangsalan writing skill result through implementing make a match model and Macromedia Unity to XI Science 3 students of SMA Negeri 1 Ngemplak Boyolali. This research is a classroom action research (CAR) with 2 cycles. Each cycle contains of 4 stages, namely ; action plan, conduct action, observation and interpretation, and also analysis and reflection. Subject of this research are the students of XI science 3 of SMA N 1 Ngemplak Boyolali which contains of 36 students. The data collection techiques are observation, interview, and test. Validity data test use triangulation method and triangulation data souce. Data analysis techniques are descriptive comparative and critical analysis. The result of this research indicate that the implementation of make a match model and macromedia unity can increase the quality of learning process in writing wangsalan and students’ wangsalan writing skill result to XI science 3 students of SMA N 1 Ngemplak Boyolali. The result can be proven since preaction until cycle 2 in preaction, the average of learning qualiti is about 2,25. Then in cycle I learning quality becomes 2,56, and in the end of cycle II it increase becomes 3,29 or in other words it is a good category. Quality of students writing wangsalan skill also indicate an improvement, in preaction students who get minimum standard score is about 11,1%, then in cycle I it becomes 55,56% and in the end of cycle 2 becomes 77,78%.